2017
DOI: 10.21873/anticanres.11833
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of RanBPM Is Associated with Poorer Survival from Lung Cancer and Increased Proliferation and Invasion of Lung Cancer Cells In Vitro

Abstract: Increased expression of RanBPM associates with postponed disease progression and better prognosis. RanBPM plays an inhibitory role in regulating proliferation and invasion of lung cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
(36 reference statements)
3
7
1
Order By: Relevance
“…However, RANBP9 appears to be rarely mutated and mostly overexpressed rather than downregulated in all types of cancers (Table S3). A recent analysis of a cohort of stage I and II LC patients suggested a positive correlation of higher levels of RANBP9 mRNA with better LC prognosis [37] in apparent contrast with our current findings. However, this latter study was exclusively based on mRNA expression and highly biased for early stage cases.…”
Section: Discussioncontrasting
confidence: 99%
“…However, RANBP9 appears to be rarely mutated and mostly overexpressed rather than downregulated in all types of cancers (Table S3). A recent analysis of a cohort of stage I and II LC patients suggested a positive correlation of higher levels of RANBP9 mRNA with better LC prognosis [37] in apparent contrast with our current findings. However, this latter study was exclusively based on mRNA expression and highly biased for early stage cases.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study revealed that RANBP9 may be a potential anti-oncogene in CRC. These results were consistent with studies on osteosarcoma, lung and gastric cancer (10–13).…”
Section: Discussionsupporting
confidence: 93%
“…The present study demonstrated that RANBP9 exhibited an inhibitory role in CRC, yet it remains unclear why malignant cells overexpress RANBP9. Similar phenomena have been observed in osteosarcoma, lung and gastric cancer (10–13). Cancer cells are associated with different sets of oncogenes and tumor suppressor genes that are normally involved in stabilizing negative feedback loops.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As RanBPM downregulation was previously reported to result in increased cellular proliferation [21,26], we evaluated whether the loss of RMND5A could also confer similar properties. Comparison of growth curves of wild-type (WT) and three different RMND5A CRISPR knockout HEK293 clonal derivatives showed that control cells slowed down after four days, whereas cells lacking RMND5A proliferated markedly faster starting at day 3 (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%